Bioactive Phenolic Compounds and Hydroxy Acids- Classification, Chemistry, Functional Properties and Therapeutic Applications - R. Chandrasekar; B. Sivagami; Shaik Asna Hayath; N. Sunandha; R. Jesline Mercy; P. Monica; S. Umamaheshwari (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
This chapter encompasses the chemistry, classification, mechanisms of action, functions and applications of hydroxy acids and Phenolic compounds. Phenolic compounds are important active phytoconstituents present in fruits and vegetables as naturally occurring bioactive compounds present in plants with antioxidant activities. Phenolic acids can be categorized into different type’s hydroxy benzoic acids and hydroxy cinnamic acids. Hydroxy acids are various types present in fruits in the form of \(α\)-Hydroxy acids and \(β\)-Hydroxy acids. Hydroxy acids can be classified into \(α\)-Hydroxy acids and \(β\)-Hydroxy acids which include lactic acid, citric acid, malic acid, tartaric acid, succinic acid. Phenolic compounds are categorized into hydroxy benzoic acid and hydroxy cinnamic acid of various forms such as gallic acid, vanillic acid, caffeic acid, syringic acid, coumaric acid, ellagic acid, transcinnamic acid and many more. Phenolic compounds are natural occurring secondary metabolites present in plants. They are abundant in plants their biological activity is vast they have high therapeutic value against many diseases which include cardiovascular diseases, anti cancer, neurological disorders, skin diseases and various other acute and chronic diseases. They are therapeutically active and they have antioxidants, free radical scavenging activity. These compounds possess active phytoconstituents, they are potent active constituents found in many plants, fruits and vegetables. They are more efficacious against many diseases and they are potent active constituents present in many medicinal plants. They have less side effects and low toxicity. Still significant research is needed to prove the efficacy of these compounds and to improve the therapeutic activities through preclinical studies and human clinical investigation.